Frontline Science: Escherichia coli use LPS as decoy to impair neutrophil chemotaxis and defeat antimicrobial host defense. Issue 6 (8th August 2019) - Kondo, Yutaka; Ledderose, Carola; Slubowski, Christian J; Fakhari, Mahtab; Sumi, Yuka; Sueyoshi, Koichiro; Bezler, Ann-Katrin; Aytan, Dilan; Arbab, Mona; Junger, Wolfgang G
Abstract: Bacterial infections and sepsis are leading causes of morbidity and mortality in critically ill patients. Currently, there are no effective treatments available to improve clinical outcome in sepsis. Here, we elucidated a mechanism by which Escherichia coli ( E. coli ) bacteria impair neutrophil (PMN) chemotaxis and we studied whether this mechanism can be therapeutically targeted to improve chemotaxis and antimicrobial host defense. PMNs detect bacteria with formyl peptide receptors (FPR). FPR stimulation triggers mitochondrial ATP production and release. Autocrine stimulation of purinergic receptors exerts excitatory and inhibitory downstream signals that induce cell polarization and cell shape changes needed for chemotaxis. Here we show that the bacterial cell wall product LPS dose-dependently impairs PMN chemotaxis. Exposure of human PMNs to LPS triggered excessive mitochondrial ATP production and disorganized intracellular trafficking of mitochondria, resulting in global ATP release that disrupted purinergic signaling, cell polarization, and chemotaxis. In mice infected i.p. with E. coli, LPS treatment increased the spread of bacteria at the infection site and throughout the systemic circulation. Removal of excessive systemic ATP with apyrase improved chemotaxis of LPS-treated human PMNs in vitro and enhanced the clearance of E. coli in infected and LPS-treated mice. We conclude that systemic ATP accumulation in response to LPS is a potential therapeutic target to restore PMN chemotaxis and to boost the antimicrobial host immune defense in sepsis. Graphical Abstract: LPS causes dysregulated ATP release, which interferes with autocrine purinergic signaling mechanisms needed for neutrophil chemotaxis and antimicrobial host defense.